IMPORTANCE OF AFFECTION IN TEACHING YOUNGER CHILDREN - Pratistha Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The cultivation of a sense of proximity, trust, and emotional attunement in interpersonal interactions requires the provision of care for the connections involved (Noddings 2013). Because of how dependent children's development and education are on the kind of care described here, this is obligatory (Cekaite 2010; Taggart 2016). In early childhood education, one of the most important responsibilities that teachers have is to provide their students with care. This is as a result of the fact that it provides a constructive contribution to the children's well-being, which is a precondition for the children's academic development and personal development. In relational conceptualizations of care, fulfilling the requirements of intimacy and closeness, in addition to moral manifestations of empathy and compassion, may be accomplished using a range of verbal and non-verbal means (Bergnehr and Cekaite 2018; Hundeide 2007; Keane 2016; Noddings 2013).